The sun won't come out tomorrow : the dark history of American orphanhood - Martin, Kristen (Bold Type Books, 2025)
"The orphan story has been mythologized: Step one: While a child is still too young to form distinct memories of them, their parents die in an untimely fashion. Step two: Orphan acquires caretakers who amplify the world's cruelty. Step three: Orphan escapes and goes on an adventure, encountering the world's vast possibilities. The Sun Won't Come Out Tomorrow upends this. Pairing powerful critiques of popular orphan narratives, from Annie to the Boxcar Children to Party of Five, journalist Kristen Martin explores the real history of orphan-hood in the United States, from the 1800s to the present. Martin reveals the religious charity and mission that was the core of the first orphanages (one that soon changed to profit), the orphan trains that took parentless children out West (often without a choice), and the inherent racism that still underlies the United States' approach to child welfare. Through a combination of in-depth archival research, memoir (Martin herself lost both her parents when she was quite young), and cultural analysis, The Sun Won't Come out Tomorrow is a compellingly-argued, compassionate book that forces us to reconsider autonomy, family, and community. Kristen Martin delivers a searing indictment of America's consistent inability to care for those who most need it"--